2003
DOI: 10.1007/s00419-002-0238-5
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic response of a crack in a functionally graded interface of two dissimilar piezoelectric half-planes

Abstract: In this paper, the dynamic anti-plane crack problem of two dissimilar homogeneous piezoelectric materials bonded through a functionally graded interfacial region is considered. Integral transforms are employed to reduce the problem to Cauchy singular integral equations. Numerical results illustrate the effect of the loading combination parameter k, material property distribution and crack configuration on the dynamic stress and electric displacement intensity factors. It is found that the presence of the dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Ueda and Mukai [11] investigated the plane fracture problem of a layered medium with graded interfacial zone. Chen et al [12] analyzed the dynamic anti-plane crack problem of two dissimilar homogeneous piezoelectric materials bonded through a graded interfacial zone. Wang et al [13] put forth a linear multi-layered model for fracture analysis of a graded interfacial zone.…”
Section: Introductionmentioning
confidence: 99%
“…Ueda and Mukai [11] investigated the plane fracture problem of a layered medium with graded interfacial zone. Chen et al [12] analyzed the dynamic anti-plane crack problem of two dissimilar homogeneous piezoelectric materials bonded through a graded interfacial zone. Wang et al [13] put forth a linear multi-layered model for fracture analysis of a graded interfacial zone.…”
Section: Introductionmentioning
confidence: 99%
“…Jin et al (2003) solved the propagation problem of an antiplane moving crack in a function graded piezoelectric strip. Chen et al (2003a) studied the dynamics response of a crack in a functionally graded interface of two dissimilar piezoelectric half-planes. They found that the presence of the dynamic electric field could impede or enhance the crack propagation depending on the time elapsed and the direction of the applied electric impact.…”
Section: Introductionmentioning
confidence: 99%
“…The investigation in Ref. [5] was the dynamic fracture of a crack in a nonhomogeneous interface. All of these papers considered the time-dependent crack tip field in nonhomogeneous materials.…”
Section: Introductionmentioning
confidence: 99%